Impact of corporate governance practices on corporate social responsibility: evidence from listed banks, finance and insurance companies in Sri Lanka / Lingesiya Kengatharan and Thangarasa Sivakaran. - Kengatharan, Lingesiya; Sivakaran, Thangarasa (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2019)
The objective of this study is to examine the impact of corporate governance practices on corporate social responsibility of the listed banks, finance and insurance companies in Sri Lanka over the period of 2013 to 2017. A sample of 20 firms out of 72 banks, finance and insurance firms listed on the Colombo Stock Exchange was considered for this study. The study utilized secondary data which were collected from annual reports of the sampled firm. Corporate social responsibility was measured by a 40-item disclose index. Corporate governance practices were measured by board size, board independence, women on board and size of audit committee. Return on assets and firm size were considered as control variables. Results of the study revealed that independent directors, return on assets and firm size have significantly positively influenced corporate social responsibility. Board size, women on the board and size of audit committee have not shown any significant impact on corporate social responsibility. The result of this study is deemed to benefit external investors and shareholders who will be able to know that how the firm committed their Corporate Social Responsible activities rather than profit maximization. Further the finding is useful for interested people such as public, government, and other financial institutions. Moreover, it will help to future researchers for further investigation related to this topic.